(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In the rapidly evolving digital era, small and medium-sized enterprises (SMEs) face increasing pressure to adopt and implement digital transformation to remain competitive. This research explores how management consulting services enable SMEs to strengthen their digital capabilities and navigate transformative change. Semi-structured qualitative expert interviews with 20 experts from the Baltic States provide valuable insights into these businesses' challenges and opportunities. The experts come from diverse professional backgrounds, including management consulting, venture capital, information technologies, finance, and professional services related to digital transformation. Qualitative comparative analysis reveals both unique perspectives and shared challenges across these groups. All experts have extensive experience working with SMEs. Key findings highlight significant barriers to digital transformation, such as limited digital skills, financial constraints, capacity issues, and insufficient know-how. Time scarcity and difficulties in maintaining strategic focus further compound these challenges. The research emphasizes the evolving role of management consulting providers, who must adapt their methodologies to meet the shifting technological landscape. The study underscores the pivotal role of management consulting in bridging the digital readiness gap for SMEs. Conclusions indicate that consultants guide businesses through complex transformation processes by offering tailored strategies, facilitating skill development, and optimizing resources. Executive insights reveal a pressing need for accessible and scalable consulting solutions to address the digital divide among smaller enterprises. This research contributes to understanding how consulting services foster digital growth in SMEs and highlights the critical need for innovative consulting approaches in the digital age, especially in the Baltic States. The findings are particularly relevant for policymakers, consultants, and SME leaders striving to enhance competitive strategy and drive digital transformation.